Evaluation of the Truvian Easy Check COVID-19 IgM/IgG Lateral Flow Device for Rapid Anti-SARS-CoV-2 Antibody Detection. Issue 2 (2nd November 2020) - Chan, Clarence W; Shahul, Sajid; Coleman, Cheyenne; Tesic, Vera; Parker, Kyle; Yeo, Kiang-Teck J
Abstract: Objectives: To evaluate the analytical and clinical performance of the Truvian Easy Check coronavirus disease 2019 (COVID-19) IgM/IgG anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody test. Serologic assays have become increasingly available for surveillance through the Food and Drug Administration emergency use authorization in the ongoing COVID-19 global pandemic. However, widespread application of serologic assays has been curbed by reports of faulty or inaccurate tests. Therefore, rapid COVID-19 antibody tests need to be thoroughly validated prior to their implementation. Methods: The Easy Check device was analytically evaluated and its performance was compared with the Roche Elecsys anti-SARS-CoV-2 antibody assay. The test was further characterized for cross-reactivity using sera obtained from patients infected by other viruses. Clinical performance was analyzed with polymerase chain reaction-confirmed samples and a 2015 prepandemic reference sample set. Results: The Easy Check device showed excellent analytical performance and compares well with the Roche Elecsys antibody assay, with an overall concordance of 98.6%. Clinical performance showed a sensitivity of 96.6%, a specificity of 98.2%, and an overall accuracy of 98.1%. Conclusions: The Easy Check device is a simple, reliable, and rapid test for detection of SARS-CoV-2 seropositivity, and its performance compares favorably against the automated Roche Elecsys antibody assay.